IS INDIAN BANKS READY TO MANAGE IN A VUCA WORLD? - Jindal, Priya (International Journal of Advanced Science and Technology, 2019)
In a globally interconnected economy, events are moving faster nowadays as compare to previous times; therefore, the communication instruments are quicker and smaller. There is a very little scope of their mitigation before they become superior. Speed of crafting and delivering mitigation strategies is essential. The global environment is changing rapidly and becomes more and more unstable and unpredictable due to a variety of factors and impact of technology. On the basis of past data, historical tools and techniques of forecasting; it is no longer possible to glance the future and the future experiences. The advancement in the world economy has strained latest innovations and enhanced the quantity of choices in all types of business organizations (Mack et. al, 2015). “The Age of Jugglers” is the title of V.U.C.A. of the Harvard Business Manager Blog. Nowadays, previous and current accomplishments cannot be transformed into potential successes. The VUCA replica was originally invented by the American military and adopted by organizations after the financial and economic crisis of 2008 (Kinsinger & Walch, 2012). For several years, VUCA become popular as it envelop various dimensions of the “uncontrollable” environment.